Conditioned Medium From Human Amniotic Mesenchymal Stromal Cells Limits Infarct Size and Enhances Angiogenesis. (30th March 2015) - Danieli, Patrizia; Malpasso, Giuseppe; Ciuffreda, Maria Chiara; Cervio, Elisabetta; Calvillo, Laura; Copes, Francesco; Pisano, Federica; Mura, Manuela; Kleijn, Lennaert; de Boer, Rudolf A.; Viarengo, Gianluca; Rosti, Vittorio; et al.
Abstract: : The paracrine properties of human amniotic membrane-derived mesenchymal stromal cells (hAMCs) have not been fully elucidated. The goal of the present study was to elucidate whether hAMCs can exert beneficial paracrine effects on infarcted rat hearts, in particular through cardioprotection and angiogenesis. Moreover, we aimed to identify the putative active paracrine mediators. hAMCs were isolated, expanded, and characterized. In vitro, conditioned medium from hAMC (hAMC-CM) exhibited cytoprotective and proangiogenic properties. In vivo, injection of hAMC-CM into infarcted rat hearts limited the infarct size, reduced cardiomyocyte apoptosis and ventricular remodeling, and strongly promoted capillary formation at the infarct border zone. Gene array analysis led to the identification of 32 genes encoding for the secreted factors overexpressed by hAMCs. Among these, midkine and secreted protein acidic and rich in cysteine were also upregulated at the protein level. Furthermore, high amounts of several proangiogenic factors were detected in hAMC-CM by cytokine array. Our results strongly support the concept that the administration of hAMC-CM favors the repair process after acute myocardial infarction. Significance: The demonstration that stem cells repair infarcted hearts mainly through paracrine mechanisms represents a potential breakthrough. Characterization of therapeutic paracrine mediators could lead to the possibility of treating acute myocardial infarction (AMI) with a single stem cell-derived molecule or a mixture. Compared with cell therapy, this approach would be technically easier to translate to the bedside. An even more straightforward strategy consists of the administration of the entire stem cell secretome (i.e., conditioned medium [CM]). Despite these potential advantages, this approach has not been thoroughly investigated using human cells. This study shows that CM of fetal stromal cells (human amniotic membrane-derived mesenchymal stromal cell [hAMC]-CM), derived from an ethically acceptable source such as the placenta, can repair infarcted hearts without the need for any manipulation. The use of hAMC-CM might be readily translated to the clinical arena in the setting of AMI upon demonstration of its effectiveness in a large animal model. Abstract : The goal of this study was to elucidate whether human amniotic membrane-derived mesenchymal stromal cells (hAMCs) can exert beneficial paracrine effects on infarcted rat hearts. In particular, the administration of hAMC-conditioned medium repaired ischemic damage through cardioprotection and angiogenesis. Finally, several putative active paracrine mediators that might account for the effects observed were identified by gene and protein arrays.